ARAH KEBIJAKAN HUKUM (LEGAL POLICY) KETENAGAKERJAAN BARU PASCA PUTUSAN MAHKAMAH KONSTITUSI NO. 168/PUU-XXI/2023: DARI INKONSISTENSI NORMA MENUJU KEADILAN SOSIAL - Yosep Ubaama Kolin; Hery Chariansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Historically, labor law policy in Indonesia has exhibited acute normative inconsistency, driven by the persistent tension between safeguarding workers' welfare and accommodating investment demands. This inconsistency culminated in the enactment of Law No. 6 of 2023 on Job Creation, which adopted a flexible labor market approach, thereby triggering the commodification of labor and a serious constitutional crisis. The issuance of the Constitutional Court Decision Number 168/PUU-XXI/2023 serves as a landmark piece of creative jurisprudence and a constitutional